TGF-β-Induced CD8+CD103+ Regulatory T Cells Show Potent Therapeutic Effect on Chronic Graft-versus-Host Disease Lupus by Suppressing B Cells - Haowen Zhong; Haowen Zhong; Ya Liu; Zhenjian Xu; Zhenjian Xu; Peifeng Liang; Peifeng Liang; Hui Yang; Hui Yang; Xiao Zhang; Xiao Zhang; Jun Zhao; et al. (Frontiers in Immunology, 2018)
Lupus nephritis is one of most severe complications of systemic erythematosus lupus and current approaches are not curative for lupus nephritis. Although CD4+Foxp3+ regulatory T cells (Treg) are crucial for prevention of autoimmunity, the therapeutic effect of these cells on lupus nephritis is not satisfactory. We previously reported that CD8+CD103+ Treg induced ex vivo with TGF-β1 and IL-2 (CD8+CD103+ iTreg), regardless of Foxp3 expression, displayed potent immunosuppressive effect on Th cell response and had therapeutic effect on Th cell-mediated colitis. Here, we tested whether CD8+CD103+ iTreg can ameliorate lupus nephritis and determined potential molecular mechanisms. Adoptive transfer of CD8+CD103+ iTreg but not control cells to chronic graft-versus-host disease with a typical lupus syndrome showed decreased levels of autoantibodies and proteinuria, reduced renal pathological lesions, lowered renal deposition of IgG/C3, and improved survival. CD8+CD103+ iTreg cells suppressed not only T helper cells but also B cell responses directly that may involve in both TGF-β and IL-10 signals. Using RNA-seq, we demonstrated CD8+CD103+ iTreg have its own unique expression profiles of transcription factors. Thus, current study has identified and extended the target cells of CD8+CD103+ iTreg and provided a possible application of this new iTreg subset on lupus nephritis and other autoimmune diseases.